Strategi Guru PAI Dalam Membimbing Pengamalan Ajaran Agama Islam Pada Siswa SDN 2 Galagamba Ciwaringin Cirebon - Surtini, Surtini; Na’imah, Farida Ulvi; Muslihun, Muslihun (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
This research aims to analyze the learning strategies used by teachers in guiding the practice of Islamic teachings among students at SDN 2 Galagamba. This research is qualitative research with a case study approach. Data was collected through observation, interviews, and documentation. The research results show that teachers use a variety of learning strategies, methods, and techniques, such as card match, reading aloud, card sorting, inquiry, group discussion, simulation, demonstration, and "everyone is a teacher here." These strategies facilitate students' active involvement in the learning process so that they can understand Islamic Religious Education subject matter in depth and practice the values ??of religious teachings in everyday life. Students are able to understand the subject matter well, answer questions, do assignments, read the Koran with correct recitation, believe in the pillars of faith, show commendable behavior, avoid disgraceful actions, understand Islamic law regarding food sources, and understand the history of the Prophet Muhammad SAW and history of Islamic da'wah. The findings of this research are in line with the principles of effective learning, constructivist learning theory, and previous research. However, there is still room for improvement and refinement of learning practices in the future, such as the development of more innovative and contextual strategies, increasing teacher skills, more active student involvement, integration of holistic learning approaches, and continuous evaluation and reflection. The success of Islamic religious education also requires support from various parties, such as the government, schools, parents, and society.